Corporate Criminal Liability for Environmental Damage: A Juridical Analysis of Recent Cases and Normative Challenges - Aris Krisdiyanto; Amir Raza; Roya Zahir (Yayasan Adra Karima Hubbi, 2025)
Background. Corporate criminal liability for environmental damage represents a growing area of concern in legal discourse, especially as industrial expansion continues to exert profound ecological and social consequences. The current legal framework in Indonesia, though progressive in recognizing corporate accountability under Law No. 32 of 2009 on Environmental Protection and Management, remains inconsistent in enforcement and interpretation. Purpose. The study aims to analyze the juridical construction of corporate criminal liability for environmental harm by examining recent judicial decisions and identifying normative challenges that hinder effective application. Method. The research employs a qualitative juridical-normative approach, focusing on statutory interpretation, court rulings, and doctrinal analysis, supported by case studies involving corporate environmental violations between 2018 and 2023 Results. The findings reveal that enforcement inconsistencies stem from vague statutory definitions, limited institutional coordination, and judicial reluctance to impose criminal sanctions on corporate entities. The analysis also highlights the absence of clear parameters for attributing mens rea and corporate culpability within collective decision-making structures. Conclusion. The study concludes that achieving environmental justice requires reforming Indonesia’s legal doctrine through clearer legislative standards, stronger prosecutorial mechanisms, and incorporation of restorative justice principles. This transformation is essential for aligning environmental governance with sustainable development and corporate accountability.